New Insights into Iron Metabolism and Deficiency - Angel de Francisco; Kai-Uwe Eckardt; Tomas Ganz; Jolanta Małyszko (European Medical Journal Nephrology, 2016)
The symposium provided an overview of the prevalence of iron deficiency and the associated disease burden in patients with chronic kidney disease (CKD). Prof Kai-Uwe Eckardt gave an overview of the prevalence of iron deficiency in patients with CKD not undergoing dialysis and addressed the challenge of diagnosing iron deficiency in this patient population based on the definitions currently used. Prof Tomas Ganz then reviewed the pathophysiology of iron metabolism, and explained the complex interplay of hepcidin in making iron available for erythropoiesis. The symposium concluded with a presentation from Prof Jolanta Małyszko who reviewed the methods of determining iron status among patients with CKD and compared data on the benefits and risks of intravenous (IV) and oral iron therapy.